The Role of Fintech and Green Investment in Driving Sustainable Transactions - Cindi Safitri; Muhammad Iqbal Fasa (Scimadly Publishing, 2024)
The role of fintech in driving sustainable transactions and green investments around the world is increasingly important as the need for environmentally friendly financial solutions increases. Fintech does this by making products and services more accessible and encouraging wider participation in the green economy. Financial technology, or fintech, through inclusive and effective digital platforms helps more people access green financing. Fintech technologies help reduce carbon footprints by replacing resource-intensive conventional financial processes with digital-based technologies. In addition, fintech encourages green investments by offering services such as crowdlending for renewable energy projects, tokenization of environmentally friendly assets, and desire-based portfolio monitoring applications. Partnerships between fintech, regulators, and the conventional financial sector are essential to building an ecosystem that supports the transition to a low-carbon economy. This article discusses the strategic role of fintech in driving global green investments and sustainable transactions, the issues faced, and opportunities to achieve the sustainable development goals (SDGs) in the future.